Incidencia del apoyo municipal a la asociación de agroproductores de la parroquia de Pintag a partir del año 2013 - Arias Cárdenas, Adela Margarita (2016)
The present work represents an effort to enhance the process for creating The Association of Agricultural Producers located in San Isidro’s neighborhood, the positive impact related with the participation of Municipality of Quito during the process, mainly during 2013-2015, contributing to the sustainability of the experience regarding organic agriculture in the household level. San Isidro’s neighborhood does not have a different experience as the entire agricultural sector in Ecuador had has, since lack of modernization, training and extra effort that small farmers have to face, makes agriculture activities neglected and lose importance in the daily activities of the local habitants, in addition local farmers face loss of production due to environmental and climatic factors such as extremely long summer or fall of hail and frost as well, more over reactivation of the activity of Cotopaxi Volcano have led to increased migration from rural to urban areas leaving the source of production. In this context Municipality of Quito has been working on local associations of small farmers at the family level with the objective to promote local production, product commercialization through trade fairs and minimal mechanization of agriculture, and the promotion of network-agricultural production for benefit of these sectors through partnership and in a later stage to the agro-ecological tourism. Systematizing this experience looks for empowering the strengthening and improvement of the organization process regarding associations of small farmers in the local area for the creation of a historical memory which strengthen and improves the partnership in common-solidarious work and the defense of food sovereignty and environmental protection.